Uniqueness of approximate solutions of the Beltrami equations - Kolomoitsev, Yu.S.; Ryazanov, V.I. (Труды Института прикладной математики и механики, 2009)
We introduce a notion of an approximate solution to the Beltrami equations, obtain some properties of such solutions and show that the approximate solution is unique up to pre-composition with a conformal mapping.